Strategi Pengembangan Arboretum Berbasis Arsitektur Ekologis di Hutan Pinus Pracimantoro Wonogiri - Bima Surya Limenta (ARSITEKTURA, 2021)
Pracimantoro sub-district has quite high tourism potential but has not been utilized properly to improve the regional economy of Wonogiri Regency. The development of pine forests into arboretum designs is the right choice in realizing edu-tourism that pays attention to natural conservation through ecological concepts. This concept applies a forest area design with attention to environmental sustainability and forest conservation. The arrangement of pine forest tourism areas is oriented to an emphasis on preserving nature, preserving local culture, and empowering the surrounding community. The research method used is qualitative and quantitative analysis based on data from various sources. The results of this study are recommendations for the benefits of arboretum development for the Pracimantoro sub-district.